Colorimetric Sensor of Hg(II) Ion from AgNPs-MO Quantified Using DIC with ED Equation Approach - Thohir, Muhammad Bakhru; Tiyas, Windi Pangesti Kusumaning (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Mercury is one of the heavy metals that has high toxicity, not only for the environment but also for human health. Mercury is found in many cosmetic products; unfortunately, for people who do not understand the dangers of mercury cosmetic ingredients, their skin will become red rashes. The novelty of this article is to use colorimetric sensor for mercury combined with Digital Image Colorimetry (DIC). The image is captured with the the smartphone camera and quantified using the Euclidean Distance (ED) Equation approach. In addition, the synthesized AgNPs also use the green synthesis method with natural materials as reducing agents and stabilizers. Therefore, the purpose of this study is to determine the best synthesis conditions and determine the detection performance of mercury (II) ions. The research began with the synthesis of mercury detection substances, namely silver nanoparticles reduced and stabilized by Moringa oleifera leaf extract (AgNPs-MO). In this study, it was found that silver nanoparticles began to form at 1 hour accompanied by heating at 120°C using a hotplate, while 6 hours when without heating. The optimum pH condition is 10. This mercury detection method has good sensitivity and accuracy values, with RSD values of less than 1% for each analyte in 5 repetitions.